MEMBANGUN KOMUNIKASI BERBASIS KESETARAAN GENDER MELALUI MEDIA ONLINE - Dita Nurmadewi (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2025)
Gender equality remains an issue in Indonesia due to the deeply rooted patriarchal culture in society. Online media, as a form of digital communication, has the potential to be a platform for voicing various issues related to gender equality. However, online media often continues to portray women as objects of gender-biased discourse. This study aims to analyze strategies that online media can adopt to build gender-equal communication. The research employs a qualitative method through a literature review. Data analysis is conducted using a descriptive qualitative approach with an interactive model. The findings indicate that, although efforts have been made to establish more inclusive gender-equal communication, gender bias is still found in some content and narratives presented by online media. Strategies that online media can adopt in building gender-equal communication include presenting content and narratives that do not marginalize women as mere objects, strengthening digital literacy through content and discussion spaces in online media, and granting women the freedom to voice gender equality through digital platforms. Keywords: Communication, Gender Equality, Online Media.